THE GOLDEN HORDE: HISTORICAL PREDECESSORS AND SUCCESSORS (historiography aspect) - Tashagil, A.; Maydanaly, Zere; Bizhanova М. (Journal of history, 2018)
The problems of the history of the Golden Horde are relevant not only to Kazakhstan researchers but also to scholars from the post-Soviet countries, who demonstrate great interest in the problem. Various aspects are in the process of scientific comprehension by specialists in the study of nomadic associations and their historical predecessors and successors. The historiographical review is devoted to the analysis of research of scientists on this issue. Researchers from different countries perceive the problem from different and, at times, directly opposite points of view. The study of various scientific positions, the analysis of all major modern trends makes it possible to compile the most complete picture of the scientific research of the history of the Golden Horde.